Determinants to Credit Decision of Low-Income Muslim During Pandemic Crisis - Swastika, Putri; Sari, Reonika Puspita; Laili, Nur (Universitas Mercu Buana, 2022)
Pandemic crisis sets many challenges to the economy, including depriving income and consumption level. In a suburbs Muslim area in Metro City, Indonesia, RT038/RW008 called the “Pinggiran Ledeng” (“skirt of irrigation”), henceforth Pingled, lived about 50 households. All of them are muslim and classified as low-income households, while 35 households are strangled in interest-rate bearing debted. This group has lost their source of income at a significant rate, and must sustain daily need using unavoidable interest-rate bearing debt. Their creditors are private loans harks and/or registered financial institutions. This paper aims to unveil what makes them underwent credit-decision in crisis settings. Understanding these components are equally important as to alleviate their economic burden through goods and cash subsidies, because poor financial behavior is a common gate to a vicious cycle of debt trap and endless poverty. This research finds the following: (1) during a crisis, emotion bias, attitude, and herding are positively significant to explain how Pingled community members take interest-rate bearing debt. Secondly, the major determinant is herding behavior, and to lesser degree are attitude and bias. Practical and policy implications are provided.